Method of multi-modal parametrical robust optimization of digital flight control systems - Tachynina, O.M.; Abramovych, O.O.; Bilak, N.V.; Klipa, A.M. (Problems of Informatization and Management, 2025)
In this paper it is proposed a method for achieving a trade-off between performance and robustness in the design of digital control systems for dynamic plants described by nominal and parametrically perturbed models. The design process accounts for both deterministic and stochastic cases. The developed method is based on the application of a multi-model Н2/Н robust optimization approach specifically for digital systems. The robust parametric optimization procedure is conducted in an interactive mode until the system's performance and robustness meet the specified requirements. The effectiveness of the developed multi-model parametric robust optimization method for digital flight control systems is validated through the synthesis of a digital heading stabilization system for a small UAV.